Pengaruh Kepemimpinan Transformasional, Supervisi Akademik dan Komitmen Kerja Terhadap Disiplin Guru SDN di Kecamatan Banjarmasin Selatan - Trisno Aji; Aslamiah Aslamiah; Mahrita Mahrita (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the direct and indirect influence of transformational leadership, academic supervision, and work commitment on the discipline of state elementary school teachers in South Banjarmasin District. This research uses a quantitative approach. The research population was all 312 public elementary school teachers in South Banjarmasin District, with a sample of 175 people determined using proportional random sampling. Data was collected through questionnaires and documentation and then analyzed descriptively and inferentially using SPSS. The results of this research show that the variable regression coefficient values ​​are positive numbers such as the principal's transformational leadership with teacher discipline of 0.337, academic supervision with work discipline of 0.334, work commitment with teacher discipline of 0.296, transformational leadership with work commitment of 0.395, and academic supervision on work commitment of 0.495. Apart from that, there was also an indirect effect of transformational leadership on work discipline through a work commitment of 0.116 and academic supervision on teacher discipline through a work commitment of 0.146. In conclusion, there is a direct and indirect influence between transformational leadership, educational supervision and work commitment on the discipline of public elementary school teachers in South Banjarmasin District Keywords: Transformational Leadership, Academic Supervision, Work Commitment, Work Discipline